2023
DOI: 10.1002/pchj.686
|View full text |Cite
|
Sign up to set email alerts
|

State‐dependent alterations of implicit emotional dominance during binocular rivalry in subthreshold depression

Shiming Qiu,
Xu Luo,
Yuhong Luo
et al.

Abstract: Binocular rivalry, a visual perception phenomenon where two or more percepts alternate every few seconds when distinct stimuli are presented to the two eyes, has been reported as a biomarker in several psychiatric disorders. It is unclear whether abnormalities of binocular rivalry in depression could occur when emotional rivaling stimuli are used, and if so, whether an emotional binocular rivalry test could provide a trait‐dependent or state‐dependent biomarker. In the current study, 34 individuals with subthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 130 publications
0
1
0
Order By: Relevance
“…These findings extend a previous study that revealed higher gaze preference for positive images among medicated MDD patients compared to nonmedicated patients 48 . Importantly, the absence of a nonmedicated control group in our experiment raises the possibility that the observed improvement may be attributed to spontaneous recovery, or other factors, rather than a causal effect of SSRIs 49 52 .…”
Section: Discussionmentioning
confidence: 91%
“…These findings extend a previous study that revealed higher gaze preference for positive images among medicated MDD patients compared to nonmedicated patients 48 . Importantly, the absence of a nonmedicated control group in our experiment raises the possibility that the observed improvement may be attributed to spontaneous recovery, or other factors, rather than a causal effect of SSRIs 49 52 .…”
Section: Discussionmentioning
confidence: 91%